BIOREMEDIASI TANAH TERKONTAMINASI LOGAM BERAT BESI (FE) DENGAN METODE COMPOSTING - Frissilia Destania; Andy Mizwar; Muhammad Abrar Firdausy; Muhammad Firmansyah (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2026)
The continuous mining increment has caused an immense number of heavy metals in soil. Mining land which comes from Coal Mining in Taping, South Kalimantan possesses 24.113,420 mg/kg Fe rate and has exceeded the limit. The high concentration of heavy metal will inflict soil pollution and destroy the ecosystem, so there shall be cleansing. Recovery could be done by bioremediation composting which utilizes microorganism activity in the composting process in order to dissect pollution. Composting uses vegetables, leaves, and branches. This research adopt in-vessel composting method for 60 days within four composts composition, which are A (5%branches + 75%vegetables + 20%leaves), B (5%branches + 20%vegetables + 75%leaves), C (5% branches + 47,5% vegetables + 47,5% leaves), D(100% soil). This research is conducted to find out the influence of compost composition variation and contact duration to the decrement of Fe within the composting process. The number of utilized reactors of in-vessel composting are 8, each consisting of 3500mL capacity with 15 cm diameter and 20 cm height. The result of 60 days research shows changes in temperature, pH, and water level within the composting process. Fe metal removal occurred in every variation. The best composition variation and composting timestamp happened in the variation A (5%branches + 75%vegetables + 20%leaves) on the 60th day with Fe final score 7514,45 mg/kg with the decrement of removal at 51,14%.